2004
DOI: 10.1097/01.blo.0000126302.41711.eb
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy Decreases Intraarticular Temperature after ACL Reconstruction

Abstract: Cryotherapy has been shown to decrease intraarticular temperature in all regions of the knee after arthroscopy. The purpose of our study was to determine if similar declines in intraarticular temperature were seen with the use of cryotherapy after anterior cruciate ligament reconstruction, a procedure which, unlike simple arthroscopy, produces postoperative hemarthrosis. Sixteen patients had intraarticular temperatures measured for 2 hours after anterior cruciate ligament reconstruction with cryotherapy instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
0
24
0
1
Order By: Relevance
“…Cryotherapy is frequently used in orthopedics for postoperative analgesia [5][6][7][8][9][10][11][12][13][14]. Despite the above-mentioned advantages of cryotherapy, it is not clear which should be the best method to administer cryotherapy to the patients, traditional coolant, or continuous cold flow device.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cryotherapy is frequently used in orthopedics for postoperative analgesia [5][6][7][8][9][10][11][12][13][14]. Despite the above-mentioned advantages of cryotherapy, it is not clear which should be the best method to administer cryotherapy to the patients, traditional coolant, or continuous cold flow device.…”
Section: Discussionmentioning
confidence: 97%
“…Many authors highlighted the importance of an aggressive rehabilitation protocol focused on the improvement of the mid-and long-term clinical outcome following ACL surgery [5]. For this reason, it appears important to adopt measures aimed to reduce pain and edema in the immediate post-operative period to allow early mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…8,28,35,46,62,91 Studies have shown significant drops in both skin and intraarticular temperatures in the knee with the use of cold therapy after ACLR. 35,91 Certain prospective, randomized, placebo-controlled clinical trials have demonstrated a reduction in postoperative narcotic consumption and visual analog pain scores for patients treated with continuous postoperative cold therapy, whereas others have failed to show any significant effect.…”
Section: Cryotherapymentioning
confidence: 98%
“…8,28,35,46,62,91 Studies have shown significant drops in both skin and intraarticular temperatures in the knee with the use of cold therapy after ACLR. 35,91 Certain prospective, randomized, placebo-controlled clinical trials have demonstrated a reduction in postoperative narcotic consumption and visual analog pain scores for patients treated with continuous postoperative cold therapy, whereas others have failed to show any significant effect. 8,28,46,62 The basic science underlying the effectiveness of cryotherapy reveals multimodal effects, including slowing of afferent nerve conduction velocity, promotion of local vasoconstriction that decreases bleeding and edema, and a slowing of local cellular metabolism that diminishes cellular hypoxia and reduces release of inflammatory mediators.…”
Section: Cryotherapymentioning
confidence: 98%
“…Previous studies have shown that cryotherapy provides an analgesic effect and helps to decrease muscle spasms [3,4]. Furthermore, cold therapy promotes structural and functional restoration by reducing blood flow, tissue temperature, and metabolism, limiting edema formation [5,6]. More recently, cryotherapy has been extensively utilized to attenuate symptoms of exercise-induced muscle damage (EIMD) such as delayed onset muscle soreness (DOMS) and decreased strength [7][8][9].…”
Section: Introductionmentioning
confidence: 98%